An analysis of the differences between young water polo players based on indicators of efficiency - Hraste, M.; Jelaska, I.; Lozovina, M. (International Journal of Performance Analysis in Sport, 2014)
The aim of this study is the identification and explanation of parameters that describe the effectiveness of four age categories of young water polo players as well as their differences in some parameters of effectiveness. The sample for this study was 72 matches of the Croatian water polo Final Championships for the younger cadets (age under 13), cadets (age under 14), younger juniors (age under 16) and juniors (age under 19) in the 2011/12 competition season.